2017
DOI: 10.4149/bll_2017_042
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lycopene on methotrexate-induced liver injury in rats

Abstract: BACKGROUND: The aim of this study was to investigate the effects of lycopene (Lyc) on methotrexate (Mtx) induced liver toxicity in rats. METHODS: Twenty-eight male Sprague-Dawley rats were divided into four equal groups: control, Lyc, Mtx and Mtx-L: Control group: Rats were given only the vehicle. Lyc group: Rats were given Lyc (10 mg/kg) with corn oil by oral gavage for ten days. Mtx group: Rats were injected intraperitoneally with a single dose of 20 mg/kg of Mtx and given corn oil by oral gavage. Mtx-L grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
(40 reference statements)
6
16
0
Order By: Relevance
“…Moderate inflammation observed in the histological section of treated animals with infiltration of chronic inflammatory cells. The histopathological changes we achieved in this study are in consistent with the previous studies, which described severe focal necrosis accompanied by hepatic granular damage, abnormal hepatocytes rearrangement around central vein with shrunken and inflected nuclei, infiltration of mononuclear cells, vascular congestion, increased KCs activation and proliferated connective tissue in hepatic sections of those rats treated with MTX [15,20,21,34,[41][42][43]. Despite, our finding represent the moderate-severe patterns of MTX-induced liver injury and thus we described milder steatohepatitic changes [11,31,34,39,40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moderate inflammation observed in the histological section of treated animals with infiltration of chronic inflammatory cells. The histopathological changes we achieved in this study are in consistent with the previous studies, which described severe focal necrosis accompanied by hepatic granular damage, abnormal hepatocytes rearrangement around central vein with shrunken and inflected nuclei, infiltration of mononuclear cells, vascular congestion, increased KCs activation and proliferated connective tissue in hepatic sections of those rats treated with MTX [15,20,21,34,[41][42][43]. Despite, our finding represent the moderate-severe patterns of MTX-induced liver injury and thus we described milder steatohepatitic changes [11,31,34,39,40].…”
Section: Discussionsupporting
confidence: 92%
“…A total of 28 male albino Wistar rats (aged 4-6 mo and weighed 125-225 g) taken from Kut Technical Institute, University of Wasit, were maintained under non-specific pathogen-free conditions in wiremeshed cages (7 rats in each cage) with ad libitum access to water and regular diet. The animals were kept under a constant temperature 24 ± 3°C with 12:12 h light dark cycle [13][14][15]. Animal handling and housing have proceeded in accordance with the international guidelines for the care and use of laboratory animals of the National Research Council [13,14].…”
Section: Experimental Designmentioning
confidence: 99%
“…One hour after resveratrol and distilled water was administered, RMTX and MTX rat groups were injected with 2 mg/kg methotrexate intraperitoneally (i.p.). The average dose of methotrexate to produce oxidative stress in rats is 10-50 mg/kg (Omer et al 2014;Yucel et al 2017). This procedure was repeated once a day for 30 days.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…with a single dose of MTX (20 mg/kg). 2 The lycopene and the solvent were administered once a day for 5 days. At the end of this application, 6 rats from each group (MG, LMG and HCG) were euthanized with a high dose of anesthesia (50 mg/kg of thiopental sodium i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…1 It has been found that this agent, which is also frequently used in ectopic and molar pregnancy treatments, increases the level of free oxygen radicals and pro-inflammatory molecules. 2 It is also gonadotoxic and decreases the number of ovarian follicles. In this way, it is thought to cause infertility, especially in young patients.…”
Section: Introductionmentioning
confidence: 99%